Kartäuserleben in der Reichskartause Buxheim 1402 - 1812: Observanz und Bibliothek - Hogg, James; Yocum, Demetrio S.; Sulpice, Audrey (Analecta Cartusiana, 2015)
A medieval bestseller in translation : Ludolph of Saxony's Vita Christi / by James Hogg -- Petrarch's humanist writing and Carthusian monsticism : the secret language of the self, Medieval church history studies 26 / by Demetrio S. Yocum (reviewed by James Hogg) -- Tombel de Chartrose, critical edition / by Audrey Sulpice -- Classique Francais du Moyen Age 173 (reviewed by James Hogg) -- Catalogue of the Analecta Cartusiana 1970-2014